Knowledge model for integrated construction project management - Ginevičius, Tomas; Kaklauskas, Artūras; Kazokaitis, Paulius (Business: Theory and Practice, 2011)
The aim of research was to develop a Knowledge model for integrated construction project management by under-taking a complex analysis of economic, legal / regulatory, technical, technological, organizational, managerial, social, cultural, political, ethical, psychological and educational factors affecting it, and to present recommendations on increasing competitive ability. A comprehensive research into the above research object required the application and integration of different knowledge management models and theories (community of practice, social network analysis, intellectual capital, information theory, complexity science, and constructivism).